Genome-wide analysis of OPR family genes in Vitis vinifera and the role of VvOPR1 in copper, zinc tolerance - You, Shuang-Hong; Chen, Yuan-Ping; Shi, Wen-Jing; Li, Xue; Wu, Zheng; Yao, Quan-Hong (Frontiers in Plant Science, 2025)
12-oxo-phytodienoic acid reductase (OPR) is one of the key enzymes in the octadecanoid pathway, and it controls the last step of jasmonic acid (JA) biosynthesis. Although multiple isoforms and functions of OPRs have been identified in various plants, no OPR genes have been identified, and their possible roles in grapevine development and defense mechanisms remain unknown. In this study, nine VvOPR genes were identified from grapevine genome and classified into two subfamilies. Systematic analyses of the physical and chemical properties, the expression and structure of the VvOPR genes, promoter elements, and chromosome locations were performed via bioinformatics and molecular biology methods. In addition, we described the characterization of the OPRI gene VvOPR1, which was synthesized via a PCR-based two-step DNA synthesis quantification reverse-transcription (PTDS) method. VvOPR1 expression is tissue-specific and induced by various stresses. The overexpression of VvOPR1 in Arabidopsis and rice (OT) significantly increased tolerance to Cu, Zn stress, and Cu, Zn stress-induced restriction of the germination rate, root/shoot length and fresh weight was significantly alleviated in OT. In OT, VvOPR1 enhanced the photosynthetic capacity, promoted ABA synthesis and the ABA-dependent stress response pathway, improved the antioxidation capacity by increasing the activities of ROS scavengers and the expression level of the related genes, while enhancing the accumulation of proline, AsA, GSH and reducing MDA and H2O2 levels. Moreover, VvOPR1 reduced Cu2+, Zn2+ accumulation and translocation. Together, we first systematically characterized the grapevine OPR gene family and reported that VvOPR1 responded to Cu, Zn stress in an ABA-dependent manner, and was quite independent of JA synthesis and signaling. All of the above results provide an important research basis and theoretical basis for further revealing the functions of VvOPR in grapevines in the future.